PREPARING STUDENTS FOR INNOVATIVE ACTIVITIES IN PRACTICAL ART CLASSES - Jo'rayeva Samiya G'ayrat qizi; Toʻrayev Bahriddin Haydar oʻgʻli (American Journals, 2023)
This article discusses preparing students for innovative activities in practical art classes. Based on practical information, the author studied and analyzed the unique aspects of preparing students for innovative work in practical art classes based on existing scientific literature.
Keywords: Education, training, lesson, student, practical art, dishonesty, art of artistic decoration, value, tradition, national idea, innovation, innavatsio technology, pedagogical technology, methodology, beauty, not only, aesthetics, aesthetics.